Learning organization practices : a case of S.E.H.(Malaysia) Sdn. Bhd. - Liew, Siew Fah (1999)
In Malaysia, the Learning Organization (LO) paradigm has gained wider grounds in many organizations and there has been a dramatic increase in its interest. Nevertheless, confusion on the concepts of LO is still present, many people still lack or have very little knowledge on it. Furthermore, their impacts on strategic management in many organizations remain unclear, abstract and under examined. But many organizations are now opting for a shift from traditional learning to learning organization paradigm for corporate survival and competitiveness in global market. This study attempts to measure the management practices of S.E.H. (Malaysia) Sdn. Bhd. against the seven dimensions ofLO, and how this organization is transforming and embarking into learning organization based on a model developed by Watkins and Marsick (1993, 1996). The specific objectives of the study were to: 1) examine the degree of creating continuous learning opportunities at the individual level, 2) measure the degree of promoting inquiry and dialogue at the individual level, 3) identify the degree of team learning and collaboration among employees, 4) identify the degree of utilizing the systems to capture and share learning, 5) identify the degree of empowering people toward a collective vision, 6) identify the degree of connecting the organization to its environment and 7) identify the degree of the providing of strategic leadership for learning. In addition, it also measures the degree to which perceived reaction of respondents toward changes in financial performance and knowledge performance at S.E.H. (M).